Analysis of the Pregnancy Outcome in Severe Injury in Pregnant Women According to Forensic Examinations for 2008-2017 in Astana - Shatalova, Yevgeniya; Zakupova, Tolkyn; Galitskiy, Frants; Gülmen, Mete Korkut; Kaya, Kenan; Koca Yavuz, Tuğçe (The Bulletin of Legal Medicine, 2023)
Objective: Traumatic injury during pregnancy is one of the leading causes of non-obstetric or accidental maternal mortality and disability in women. The aim of the study was to evaluate the relationship between the severity of injuries in pregnant women and termination of pregnancy, which are qualified as “serious harm to health” in accordance with the conclusions of forensic medical examination in the medical injury documentation of pregnant women. Methods: The study examined retrospectively the records of forensic medical examinations of pregnant women where the bodily injury was qualified as “serious harm to health” between 2008 and 2017. The analysis of the conditions and mechanisms of occurrence of injury, the type and area of injury, and the outcome of the pregnancy was also included in the research. Results: 12 pregnant women were found to have injuries that is qualified as serious harm to health. The traffic accidents led the causes of injury with eight cases (66.7%). In the remaining cases, one of the pregnant women had mechanical injury during the fire, the other had a sexual assault with a bottle, and two cases had penetrating stab injuries. The pregnancy outcomes were as follows: intrauterine fetal death at week 30 and 35 occurred in two cases, spontaneous miscarriage at week 20 in one case and medical abortion at 6 week in one case which amounts to 33.3%. Conclusion: All cases of termination were accompanied by severe combined injuries in pregnant women and an unfavorable outcome is more often observed with polytrauma.